Joint Cross-layer Power Control and FEC Design for TCP Westwood+ in Hybrid Wireless-Wired Networks - G. Boggia; P. Camarda; A. D’Alconzo; L.A. Grieco; S. Mascolo; Houda Labiod; Mohamad Badra (New Technologies, Mobility and Security, 2007)
In Hybrid wired-wireless networks, power control algorithms and FEC techniques have to be adopted and optimized to hide the unreliability of wireless links to TCP. To achieve the expected performance gain, a joint cross-layer optimization that takes into account also TCP congestion control is required. Recently, in literature, a theoretic framework has been proposed to address this issue when New Reno TCP is used. This work extends such a recent findings to cope also with Westwood+ TCP, a recent TCP congestion control algorithm proposed for networks with high bandwidth delay products and random losses. Numerical results have shown that, for the same propagation conditions, Westwood+ TCP requires less power and FEC codes to achieve the same goodput of New Reno TCP